MicroRNA-17-5p Promotes Vascular Calcification by Targeting ANKH - Shi, Chao; Tan, Jiaorong; Lu, Jiancan; Huang, Junling; Li, Xiangqi; Xu, Jiahong; Wang, Xing (Current Neurovascular Research, 2022)
Background: MicroRNAs (miRNAs) may participate in the process of vascular calcification. However, the role of microRNA-17-5p in vascular calcification has not been clarified. In this study, we showed the effects of microRNA-17-5p on vascular calcification. Materials and Methods: Vascular smooth muscle cells (VSMCs) were transfected with miR-17-5p mimics, a miR-17-5p inhibitor or negative control (NC) using Lipofectamine 2000. Then the cells were induced by an osteogenic medium. Alkaline phosphatase (ALP) activity and mineralization were determined. Osteocalcin (OC), bone morphogenetic protein 2(BMP-2), Collagen Ia (Colla), Runx2, and ankylosis protein homolog (ANKH) gene expressions were determined by reverse transcription-polymerase chain reaction. Vascular calcification was developed using a renal failure model. Results: The ALP activity was increased when miR-17-5p mimics were transfected, whereas the miR-17-5p inhibitor reduced ALP activity (p < 0.05). The number and average area of mineral nodes in the miR-17-5p mimic group was larger than those in the corresponding control and NC groups (p < 0.05). The number and average area of the mineral nodes in the miR-17-5p inhibitor group were smaller than those in the corresponding control and NC groups (p < 0.05). Bmp2, OC, Col1a and Runx2 were higher in the miR-17-5p mimics group compared to those in the control and NC groups. ANKH expression was decreased in VSMCs with the miR-17-5p mimics and increased in VSMCs with miR-17-5p inhibitor. ANKH siRNA intervention also promoted mineralization. The miR-17-5p expression was upregulated and ANKH was down-regulated in the aortic arteries with calcification. Conclusion: Our data showed that miR-17-5p may promote vascular calcification by inhibiting ANKH expression.
Keywords: osteogenic